Understanding Chemistry for Advanced Level - Lister, Ted.; Renshaw, Janet, 1940- (Thornes, 1991)
A chemistry text for A-level students based on analysis of the latest A and AS syllabuses. It bridges many topics from GCSE and places emphasis on social, economic, environmental and technological applications of chemistry.